2015
DOI: 10.1111/ele.12469
|View full text |Cite
|
Sign up to set email alerts
|

Land use intensification alters ecosystem multifunctionality via loss of biodiversity and changes to functional composition

Abstract: Global change, especially land‐use intensification, affects human well‐being by impacting the delivery of multiple ecosystem services (multifunctionality). However, whether biodiversity loss is a major component of global change effects on multifunctionality in real‐world ecosystems, as in experimental ones, remains unclear. Therefore, we assessed biodiversity, functional composition and 14 ecosystem services on 150 agricultural grasslands differing in land‐use intensity. We also introduce five multifunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
540
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 663 publications
(580 citation statements)
references
References 45 publications
36
540
2
2
Order By: Relevance
“…Previous studies have demonstrated that local-scale (α-) biodiversity can boost multifunctionality in the real world, in addition to experimental ecosystems (8,(14)(15)(16). Here, we add evidence that both α-and β-diversity can also drive ecosystem multifunctionality at the landscape scale, and that the desired distribution of ecosystem functions across the landscape influences the importance of this relationship.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous studies have demonstrated that local-scale (α-) biodiversity can boost multifunctionality in the real world, in addition to experimental ecosystems (8,(14)(15)(16). Here, we add evidence that both α-and β-diversity can also drive ecosystem multifunctionality at the landscape scale, and that the desired distribution of ecosystem functions across the landscape influences the importance of this relationship.…”
Section: Resultsmentioning
confidence: 60%
“…However, although society seeks to maximize the delivery of potentially conflicting ecosystem services, such as food production, bioenergy generation, and carbon storage at the landscape scale (11)(12)(13), research into the relationship between biodiversity and ecosystem multifunctionality has been largely limited to local-scale studies, where diversity is manipulated in experimental plant communities. Although some studies have focused on more natural communities distributed over larger spatial extents (e.g., [14][15][16], they examined relationships between local-scale biodiversity and local-scale multifunctionality. The only previous study to investigate multifunctionality at larger scales (17) simulated artificial landscapes using data from experimental grassland communities.…”
mentioning
confidence: 99%
“…However, an advantage of our approach is that it explicitly reviews the identity of service change, rather than reducing the provision of ecosystem services into a single metric. In addition we do not apply differential weights to ecosystem services, as to do so would require community input to define values and accepted thresholds of performance (Allan et al 2015). This could be useful additional work that would allow for a more detailed quantification of trade-offs and synergies in the provision of ecosystem services.…”
Section: Implications For Policy and Decision Makingmentioning
confidence: 99%
“…This provides greater stability within a biophysical system through time, which in turn contributes to sustained provision of ecosystem services and associated social benefits. Diverse systems are expected to have high multifunctionality, which is achieved when local sites or landscapes simultaneously provide multiple ecosystem functions or services (Allan et al 2015;Byrnes et al 2014;Gamfeldt et al 2013;Wagg et al 2014). Landscapes can provide a range of ecosystem services either through provision of multifunctionality at a local scale or through spatial heterogeneity of service provision due to landscape mosaics of different ecosystems and communities, which are often shaped by social preferences (Allan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation